Factors Influencing the Success of the National Nursing Competency Examination taken by the Nursing Diploma Students in Yogyakarta - Yulia Wardani (Universitas Airlangga, 2019)
Introduction: The Indonesian government mandated the national examination for health professional in 2014. Yogyakarta was the province with the highest percentage achievement for this past five years and it was affected by many factors. This study was conducted to analyze what are the factors that influence the success in national nursing examination of three year nursing students in Yogyakarta.Methods: This descriptive correlative design with sample of 926 graduate students of three years diploma in Yogyakarta and total sampling technique was used. The data were analyzed by frequency distribution, F-test, multiple regression and R2 for the determinant analysis unit. Results:The study identified that 78.1% of the participants were female with age of 20 to 24 years old, 68.2 % were come from Yogyakarta, 96,9% had academic grade with range of 3 to 3.99. The ranges of passing grades of exam scores were 67% to 98 %, and 89% the institutions were able to achieve passing grade more than 75%. There were some significant correlations between learning strategic with mental preparation (p=0.12), the readiness of the manager (p=0.00), the place that the test was delivered (p=0.00) and the learning strategic was the most determinant predictor in success of the exam.Conclusions: A good learning strategic was the dominant factor for success of national competency and mental preparation, the readiness of the manager, the place where the test was delivered were correlated with the success of the exam.